Ag/TiO2 nano-thin films as robust heterogeneous catalyst for one-pot, multi-component synthesis of bis (pyrazol-5-ol) and dihydropyrano[2,3-c]pyrazole analogs - Maryam Fatahpour; Fatemeh Noori Sadeh; Nourallah Hazeri; Malek Taher Maghsoodlou; Mohammad Saeed Hadavi; Sahar Mahnaei (Journal of Saudi Chemical Society)
The present methodology describes two efficient, eco-friendly, and simple routes for the cascade synthesis of biologically relevant pyrazole scaffolds using Ag/TiO2 nano-thin films as a green, robust, and recyclable catalyst. Ag/TiO2 nano-thin films were successfully applied for the synthesis of bis (pyrazol-5-ol) and dihydropyrano[2,3-c]pyrazole derivatives in the one-pot, multicomponent manner. These operationally straightforward procedures have merits, including high yields of products from a simple set of readily available starting materials, eco-friendliness, and heterogeneity and reusability of catalyst. Also, it was observed that the catalyst was highly stable during the reaction and several reuse times without observable losses in catalytic performance. Keywords: Ag/TiO2 nano-thin films, Bis (pyrazol-5-ols), Dihydropyrano[2,3-c]pyrazoles, Eco-friendliness